1999
DOI: 10.3189/s0022143000003099
|View full text |Cite
|
Sign up to set email alerts
|

Mass-balance studies on Siachen Glacier in the Nubra valley, Karakoram Himalaya, India

Abstract: ABSTRACT. The hyd rological method is used to compute the m ass ba la nce ofSiachen Gl acier in th e Nubra Valley, K a rakora m Him a laya, India. The m ethod was chosen because of its suitability in rugged terra in. Analysis of precipitati on ? ata from th e glacier as a ~unc tion of altitude shows a power-law rel ationship. Accumulal10n eStimates based on thls relati onship show good ag reem ent with th e recorded precipitati on. Th e di scha rge d ata fr om the glacier sho w high runoff in th e abl ati on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 7 publications
1
35
0
Order By: Relevance
“…() for the north‐western Himalaya. Given the complexity of glacier dynamics in relation to topography, elevation and debris cover glacial dynamics will differ regionally and even locally (Bhutiyani, ; Mihalcea et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…() for the north‐western Himalaya. Given the complexity of glacier dynamics in relation to topography, elevation and debris cover glacial dynamics will differ regionally and even locally (Bhutiyani, ; Mihalcea et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Satellite‐derived images and snow cover data at different times clearly show the recession of this glacier in recent times (e.g., see Rasul, Dahe, & Chaudhry, ; Mukhopadhyay, ). Field‐based glacial mass balance studies of Siachen Glacier conducted by Bhutiyani () for a 5‐year period (1986–1991) showed negative mass balance for all years except for one (1988–1989), which experienced comparatively heavy winter snowfall amounts and comparatively low temperatures during the ablation season. Rankl et al () observed that out of 1334 Karakoram glaciers, 134 show advancing, or surging behavior with a marked increase since 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Additional verification to the present SWE reconstruction is again provided by the snow avalanche frequency in Lahaul region as recorded in tree rings [ Laxton and Smith , ]. The variability in snowfall anomalies is associated with the magnitude and frequency of snow avalanches in hilly terrains causing serious damages to life and property [ Bhutiyani , ]. The study of Himalayan cedar growth‐ring features from a site close to our study area showed that the low SWEs recorded in the 1970s in our reconstruction are consistent with fewer incidences of slope failures [ Laxton and Smith , ].…”
Section: Calibration and Reconstruction Of November–april Swe Datamentioning
confidence: 98%